2010
DOI: 10.1029/2009jb007175
|View full text |Cite
|
Sign up to set email alerts
|

A model for wet aggregation of ash particles in volcanic plumes and clouds: 1. Theoretical formulation

Abstract: [1] We develop a model to describe ash aggregates in a volcanic plume. The model is based on a solution of the classical Smoluchowski equation, obtained by introducing a similarity variable and a fractal relationship for the number of primary particles in an aggregate. The considered collision frequency function accounts for different mechanisms of aggregation, such as Brownian motion, ambient fluid shear, and differential sedimentation. Although model formulation is general, here only sticking efficiency rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
200
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 115 publications
(202 citation statements)
references
References 73 publications
(128 reference statements)
2
200
0
Order By: Relevance
“…in the vertical column, as aggregation due to the presence of ice seems is less effective. Costa et al (2010) also demonstrated how wet aggregation strongly depends on the ratio between the residence time of aggregating particles within the cloud region where liquid water exists and the time required for aggregates to form. As a result, aggregation processes are likely to be more effective in moderate explosions and small plumes than in vigorous Plinian and sub-Plinian eruptions characterized by fast ascending plumes.…”
Section: Empirical and Numerical Studies On Aggregationmentioning
confidence: 99%
See 4 more Smart Citations
“…in the vertical column, as aggregation due to the presence of ice seems is less effective. Costa et al (2010) also demonstrated how wet aggregation strongly depends on the ratio between the residence time of aggregating particles within the cloud region where liquid water exists and the time required for aggregates to form. As a result, aggregation processes are likely to be more effective in moderate explosions and small plumes than in vigorous Plinian and sub-Plinian eruptions characterized by fast ascending plumes.…”
Section: Empirical and Numerical Studies On Aggregationmentioning
confidence: 99%
“…Such a model was then implemented by Folch et al (2010) with good agreement. The models proposed by Costa et al (2010) and Folch et al (2010) demonstrate that wet aggregation is limited to the cloud region characterized by temperatures above the freezing point of water, i.e. in the vertical column, as aggregation due to the presence of ice seems is less effective.…”
Section: Empirical and Numerical Studies On Aggregationmentioning
confidence: 99%
See 3 more Smart Citations